Maternal and fetal factors influencing fetal fraction: A retrospective analysis of 153,306 pregnant women undergoing noninvasive prenatal screening - Deng, Cechuan; Liu, Jianlong; Liu, Sha; Liu, Hongqian; Bai, Ting; Jing, Xiaosha; Xia, Tianyu; Liu, Yunyun; Cheng, Jing; Wei, Xiang; Xing, Lingling; Luo, Yuan; et al. (Frontiers in Pediatrics, 2023)
Background: Genetic factors are important causes of birth defects. Noninvasive prenatal screening (NIPS) is widely used for prenatal screening of trisomy 21, trisomy 18, and trisomy 13, which are the three most common fetal aneuploidies. Fetal fraction refers to the proportion of cell-free fetal DNA in maternal plasma, which can influence the accuracy of NIPS. Elucidating the factors that influence fetal fraction can provide guidance for the interpretation of NIPS results and genetic counseling. However, there is currently no broad consensus on the known factors that influence fetal fraction. Objective: The study aimed to explore the maternal and fetal factors influencing fetal fraction. Methods: A total of 153,306 singleton pregnant women who underwent NIPS were included. Data on gestational age; maternal age; body mass index (BMI); z-scores for chromosomes 21, 18, and 13; and fetal fraction in NIPS were collected from the study population, and the relationships between fetal fraction and these factors were examined. The relationship between fetal fraction and different fetal trisomy types was also analyzed. Results: The results showed that the median gestational age, maternal age, and BMI of the pregnant women were 18(16, 20) weeks, 29 (25, 32) years, and 22.19 (20.40, 24.24) kg/m2, respectively. The median fetal fraction was 11.62(8.96, 14.7)%. Fetal fraction increased with gestational age and decreased with maternal age and BMI (P<0.001). Fetal fraction of fetuses with trisomies 21, 18, and 13 was similar to that of the NIPS-negative group. The z-scores of pregnant women with trisomy 21 and 18 fetuses were positively correlated with fetal fraction, but not with that of the trisomy 13 cases. Conclusions: The factors that influence fetal fraction need to be taken into consideration before NIPS for quality control and after NIPS for result interpretation.